2017
DOI: 10.1093/rheumatology/kex182
|View full text |Cite
|
Sign up to set email alerts
|

Functional disability and its predictors in systemic sclerosis: a study from the DeSScipher project within the EUSTAR group

Abstract: SSc patients perceive dyspnoea, pain, digital ulcers, muscle weakness and gastrointestinal symptoms as the main factors driving their level of disability, unlike physicians who emphasize objective measures of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 28 publications
1
66
1
1
Order By: Relevance
“…It has been shown that multiple factors contribute to the potentially severe disease-related manifestations and the hindrance of patients' functional capacity (37,38). Together with an extended fibrosis of the skin, joint contractures, sarcopenia, gastrointestinal and cardiopulmonary involvement, the presence of Raynaud's phenomenon and DUs have an important impact on daily life activities and work-related endeavors (8,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that multiple factors contribute to the potentially severe disease-related manifestations and the hindrance of patients' functional capacity (37,38). Together with an extended fibrosis of the skin, joint contractures, sarcopenia, gastrointestinal and cardiopulmonary involvement, the presence of Raynaud's phenomenon and DUs have an important impact on daily life activities and work-related endeavors (8,38).…”
Section: Discussionmentioning
confidence: 99%
“…The patient-centered approach to disability in scleroderma leads to the conclusion that SSc-related dyspnea often constitutes one of the main factors involved in the decrement of life quality as well as disability (47)(48)(49). According to recent data from the DeSScipher project within the EUSTAR (European Scleroderma Trials and Research) group, dyspnea and the presence of DUs emerge as major determinants of functional impairment in SSc patients (8). Other studies have reported similar findings regarding the importance of dyspnea in SSc-related quality of life (50,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such changes influence symptoms such as dyspnea, which has been found to be a major factor contributing to their disability. [33] Another key feature of the PAH-CTD is the advancing age (PAH-CTD: 55 ± 13 vs IPAH: 46 ± 15 yr) and reduced exercise capacity (V O2: PAH-CTD: 0.82 ± 0.25 and 0.87 ± 0.30 vs IPAH: 1.10 ± 0.41 l.min -1 ) during the six minute walk test. [34,35]…”
Section: Central Factors (Cardiovascular and Pulmonary)mentioning
confidence: 99%
“…A survey of 50 patients with RA-ILD at a US center found that the severity of fatigue and dyspnea were the strongest predictors of physical health impairment, while the severity of cough, fatigue, and dyspnea were the strongest predictors of mental health impairment [28]. Dyspnea has been reported by patients with SSc as one of the main factors driving their functional disability [29].…”
Section: Introductionmentioning
confidence: 99%